Digital inclusion: a case study with students with special needs - Kintschner, Fernando Ernesto; Ferreira, Denise Helena Lombardo (Revista Hipótese, 2019)
In view of the high number of disabled people of the most varied types with few opportunities to obtain employment links, this research aims to provide extension students of different undergraduate courses of a private university to give workshops and video classes about MS Office to capacitate these individuals and consequently provide opportunities for insertion into the labor market. Extension students will use the Scrum project management method to develop a Portal, containing information on jobs, curricula, games, courses, culture and video classes. The accomplishment of this research can help the employability of people with special needs, increase their autonomy and self-esteem.
Keywords: Labor market insertion; Digital inclusion; Qualification of persons with disabilities